2022
DOI: 10.3390/vetsci9020077
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin Influences FGF2 in the Developing Porcine Corpus Luteum

Abstract: Luteal angiogenesis is regulated by pro-angiogenic hormones including fibroblast growth factor 2 (FGF2) and angiopoietin 1 (Ang1), which are regulated by the adipokine leptin during development. Another adipokine, adiponectin, exhibits an inverse relationship with leptin and has been identified in the CL. Therefore, it is hypothesized that adiponectin will influence pro-angiogenic hormones in the developing porcine CL. Crossbred sows were randomly allocated to one of two days of the estrous cycle, day 5 (D5; n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 58 publications
(93 reference statements)
0
1
0
Order By: Relevance
“…Research has shown that adiponectin plays a crucial role in oocyte maturation, granulosa cell proliferation, and steroid secretion in the ovaries [23]. Additionally, adiponectin has been suggested to influence angiogenic factors in the development of porcine CL [55]. Previous studies have reported higher adiponectin levels during the follicular stage, with particularly high levels in cumulus-oocyte complexes and theca cells of dominant follicles [56].…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that adiponectin plays a crucial role in oocyte maturation, granulosa cell proliferation, and steroid secretion in the ovaries [23]. Additionally, adiponectin has been suggested to influence angiogenic factors in the development of porcine CL [55]. Previous studies have reported higher adiponectin levels during the follicular stage, with particularly high levels in cumulus-oocyte complexes and theca cells of dominant follicles [56].…”
Section: Discussionmentioning
confidence: 99%
“…Adiponectin's mRNA levels remained consistently expressed across all time points, with a downregulation at 48 h (Figure 2A). Additionally, adiponectin has been suggested to influence angiogenic factors in developing porcine CL [59]. The expression of adiponectin receptor 1 remained at low levels without significant changes.…”
Section: Discussionmentioning
confidence: 99%